PENGARUH PENDEKATAN PICTORIAL RIDDLE JENIS VIDEO TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN INKUIRI PADA MATERI GELOMBANG TERINTEGRASI BENCANA TSUNAMI - Ichy Lucia (PILLAR OF PHYSICS EDUCATION, 2013)
This research is motivated by the fact that the Padang city is in the area which allows suffered tsunami that required to improve preparedness against disaster. The learning was applied is Pictorial Riddle Approach video type in Inquiry Learning. The purpose of research is to determine the influence of Pictorial Riddle Approach video type to learning results of student in inquiry learning on wave material integrated by tsunami. The type of this research is Quasi Experimental research. The population in this research is all students of class XII at SMAN 3 Padang are listed in academic year 2012/2013. Class sample was determined by cluster random sampling technique. The instrument is used to collect data is written tests for the cognitive domain. The result of the data analysis is the learning results of student to cognitive domain for the experiment class and control class are 87.10 and 82.50. The hypothesis test for the cognitive domain is tcount > ttable at significance level 0.05 and dk 61. The conclusion is the hypothesis which states that there is influence of Pictorial Riddle Approach video type to learning results of student in inquiry learning on the wave material integrated by the tsunami in grade XII SMAN 3 Padang is acceptable.   Keywords — pictorial riddle, inkuiri, video, hasil belajar, gelombang, tsunami